Development of Virtual Reality-Based Learning Media for Product-Setting Subjects in Vocational Schools - Rahmadi, Andi; Hanafi, Ivan; Sukardjo, Sukardjo (Riviera Publishing, 2023)
The research aims to develop learning media based on Virtual Reality for the Product Management subject at SMKN 14 Jakarta. The study uses research and development methods (Research & Development) using the combined procedure reference development model between the Borg and Gall models, the Dick Carey Model), and the Hannafin and Peck Models. This model is carried out through needs analysis, design, development, testing, implementation, and maintenance. The results of this study are as follows. (In summary, the research went through several key stages: 1) The analysis stage highlighted the limitations of practical facilities for the Limited Product Arrangement subject. 2) The design phase resulted in a comprehensive design, including Virtual Reality illustrations with 3D display designs, color selection, typography, page layouts, images, videos, audio, and interface designs. 3) During the development of Virtual Reality products, the researcher processed the content into a medium using the Unity Engine application. 4) The testing phase, which included material and media testing, produced highly favorable results. Material experts rated content quality and objectives at 4.8 in the